Large Scale Synthesis of Silver Vanadate Nanowires Consolidated into Bulk Cylinder with Enhanced Antibacterial Properties - Singh, D; Lopez de Dicastillo-Bergamo, A; Patiño-Vidal, C (Elsevier B.V., 2020)
Here we report the acetonitrile mediated large scale synthesis of self-assembled bulk cylinder (length ~ 9.00 cm, diameter ~ 4.0 cm) consolidated with very long and thin β-AgVO3 nanowires and its enhanced antibacterial activity against bacteria that cause skin/respiratory infections and food poisoning etc. The use of 30 mL acetonitrile during the mixing of the reactants AgNO3 and NH4VO3 and post hydrothermal treatment at 200 °C for 12 h results the formation of bulk cylindrical structure assembled with the large number of interweaved nanowires having a minimum diameter ~ 16 nm and of undefined length ~ 10 μm. The self-assembled β-AgVO3 nanowire like structure exhibits enhanced antibacterial activity against Listeria innocua ATCC 33090, Staphylococcus aureus ATCC 25,923 and Escherichia coli ATCC 25922, as Gram-positive and Gram-negative bacteria, respectively. A concentration of 25 µg/mL of β-AgVO3 nanowires exhibits bacterial cellular inhibition of 4 logarithms reduction against all studied bacteria. © 2020 Elsevier B.V.